Análisis de características de estrés situacional a partir de rostro en trabajadores de un call center usando técnicas de procesamiento de imágenes (2022)
Burnout syndrome is the cause of a high turnover of operators in call center companies, this is mostly due to the pressure to achieve goals and endure verbal abuse by users. For this reason, a tool for the detection of situational stress through digital image processing techniques is sought. This project focuses on face segmentation with face mask and extraction of relevant features for classification.